2017
DOI: 10.1093/cvr/cvx079
|View full text |Cite
|
Sign up to set email alerts
|

Connexin37 reduces smooth muscle cell proliferation and intimal hyperplasia in a mouse model of carotid artery ligation

Abstract: The presence of Cx37 in the media layer of injured arteries restrains VSMC proliferation and limits the development of IH, presumably by interfering with the pro-proliferative effect of Cx43 and the Akt pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…Cx37 exerts a growth suppressive effect in vivo and in vitro; it suppresses vasculogenesis and angiogenesis (Allagnat et al, 2017;Fang et al, 2011) and is a potent suppressor of cancer cell proliferation (Burt et al, 2008;Morel et al, 2010). Available data (Good et al, 2012(Good et al, , 2014(Good et al, , 2011Nelson et al, 2013) suggest:…”
Section: Discussionmentioning
confidence: 99%
“…Cx37 exerts a growth suppressive effect in vivo and in vitro; it suppresses vasculogenesis and angiogenesis (Allagnat et al, 2017;Fang et al, 2011) and is a potent suppressor of cancer cell proliferation (Burt et al, 2008;Morel et al, 2010). Available data (Good et al, 2012(Good et al, , 2014(Good et al, , 2011Nelson et al, 2013) suggest:…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have suggested that DESs delay re-endothelialization, which is important for the prevention of restenosis and stent thrombosis. Intimal hyperplasia develops as a result of SMC migration and proliferation, and the accumulation of the extracellular matrix, which is a normal adaptive response in arteries against hemodynamic stress and is a characteristic feature of arterial injury healing ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) has anti-inflammatory effects and protects against neointimal hyperplasia [22]. Therefore, we assessed the expression of NO synthase mRNA by RT-PCR.…”
Section: Hucmsc-exosomes Significantly Accelerated Reendothelializatimentioning
confidence: 99%